bài đại lớp 7 khó nè

H

hiensau99

Ta có $ \dfrac{p}{m-1}= \dfrac{m+n}{p} \to p^2 = (m-1)(m+n)$

P là số nguyên tố nên $p^2$ chỉ có các ước nguyên dương là $1;p;p^2$ và $p^2>1$ (1)


Do $m;n \in N*$ nên $m-1<m+n$ (2)


Từ (1) và (2) ta có $(m-1)(m+n) = 1. p^2$

$ \to \left\{\begin{matrix} m-1 =1\\p^2= m+n \end{matrix}\right.$

$\to \left\{\begin{matrix} m =2 \\ p^2= 2+n \text{ (đpcm)} \end{matrix}\right.$


354rg5fd4b2fg4h56f1n0b0cv4b
4gn2g1kj2fg4h13g1k2n4
1n354v1jkl201n32g45
 
Last edited by a moderator:
Top Bottom